The Specific Features of Red Blood Cell Membranes in Premature Neonates Due to Multiple Pregnancy - S. A. Perepelitsa; V. A. Sergunova; O. E. Gudkova; S. V. Alekseeva (Общая реаниматология, 2014)
Objective: to substantiate the efficacy of bipolar impulses of different shapes and duration.Method. The investigation used the dynamic model II of the mammalian ventricular cardiomyocyte membrane in the guinea-pig, proposed by Luo and Rudy (1994—2000). The cardiomyocyte membrane was acted by substituting the current density of the impulse under study. The threshold impulse energy ratio considered as an integral index of the threshold action (a measure of efficiency) of an impulse measured in μA2 ms/cm4 was then calculated. A comparison was made between a classical quasi<sinusoidal impulse, a stepwise quasi-sinusoidal, rectilinear, classical trapezoidal, trapezoidally modulated (the presence of high-frequency, high-amplitude oscillations of current) impulse and its unmodulated equivalent, and a trapezoidal low<angle front tail impulse of the duration equal to that of the classical quasi-sinusoidal one. The shape of the impulses corresponded to the 100-ohm resistance of the chest. Results. The most effective impulses  proved  to  be  a  quasi-sinusoidal  stepwise  impulse  (229.6  μA2 ms/cm4 ),  next  a  classical  quasi-sinusoidal  impulse (249 μA2 ms/cm4 , +9%) and a trapezoidal low<angle front tail one (253.0 μA2 ms/cm4 , +10%). The trapezoidally modulated impulse (397 μA2 ms/cm4 , +73%) turned out to be lowest effective (in the threshold impulse energy ratio). The other  impulses  were  intermediate  between  the  above  impulses  in  the  following  order:  a  modulated  trapezoidal impulse equivalent (272.0 μA2 ms/cm4 ), next a rectilinear impulse (273.5 μA2 ms/cm4 ), and a classical trapezoidal one (307.0 μA2 ms/cm4 ).Conclusion. In terms of the excitation threshold of the Luo-Rudy model of the guinea-pig cardiomyocyte membrane, the most effective impulses are quasi<sinusoidal stepwise, next quasi<sinusoidal and trapezoidal low-angle front tail ones.